2002
DOI: 10.1097/00000539-200212000-00041
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Hemorrhagic Complications Associated with Nonsteroidal Antiinflammatory Medications in Ambulatory Pain Clinic Patients Undergoing Epidural Steroid Injection

Abstract: Previous studies performed in obstetric and surgical populations have demonstrated that antiplatelet therapy does not increase the risk of spinal hematoma associated with spinal or epidural anesthesia and analgesia. We confirm the safety of epidural steroid injection in patients receiving aspirin-like medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 16 publications
4
81
0
7
Order By: Relevance
“…The difficulty in performing a study to prove causation in this instance is related to the relatively rare incidence of epidural hematomas making the number needed for such a study unrealistic. The risk of spinal hematomas associated with neuraxial anesthesia is reported to be approximately one in 150,000 for epidural and one of 220,000 for spinal anesthesia [19,20]. Designing a study with sufficient power to prove a causal relationship between neuraxial anesthesia and the incidence of spinal hematomas is unlikely to be feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in performing a study to prove causation in this instance is related to the relatively rare incidence of epidural hematomas making the number needed for such a study unrealistic. The risk of spinal hematomas associated with neuraxial anesthesia is reported to be approximately one in 150,000 for epidural and one of 220,000 for spinal anesthesia [19,20]. Designing a study with sufficient power to prove a causal relationship between neuraxial anesthesia and the incidence of spinal hematomas is unlikely to be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of successful spinal anesthesia in the setting of dual antiplatelet therapy have been reported, and one study examining the outcomes of over 1,200 epidural steroid injections in 1,000 patients on NSAIDs has demonstrated that antiplatelet therapy does not increase the risk of spinal hematoma associated with spinal or epidural anesthesia and analgesia [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…When ASA or non-steroidal anti-inflammatory drugs (NSAIDS) are used alone, the risk of a spinal/epidural hematoma does not increase and they do not constitute a contraindication in using regional techniques. A limited number of studies in the literature demonstrate that spinal hematoma does not pose and extra risk in this group of patients CLASP (Collaborative Low-dose Aspirin Study in Pregnancy) (Collaborative Group., 1994;Horlocker et al, 1995;Horlocker et al, 2002).…”
Section: Acetylsalicylic Acid (Asa)mentioning
confidence: 99%
“…There were no spinal hematomas in a series of 1,214 patients undergoing epidural steroid injection, including 383 (32%) who were receiving antiplatelet medications. 12 However, there were 42 patients with new neurologic symptoms or worsening of preexisting symptoms that persisted for more than 24 hr after injection. Median duration of the symptoms was three days.…”
mentioning
confidence: 99%
“…10 ont rapporté que les lésions médullaires étaient la principale cause de récla-mation dans les années 1990 et qu'un important facteur associé était le bloc utilisé pour traiter la douleur chronique, y compris l'injection péridurale de stéroïde péridural. Dans une série de 1 214 patients recevant une injection péridurale de stéroïde, incluant 383 (32 %) sous médication antiplaquettaire, 12 aucun hématome rachidien n'est rapporté. Par contre, 42 patients présentaient des symptômes neurologiques ou l'aggravation de symptômes préexistants qui persistaient pendant plus de 24 h après l'injection.…”
unclassified